Implementasi Program Peningkatan Penerapan Teknologi dan Produksi Pala di Kecamatan Siau Barat Kabupaten Kepulauan Siau Tagulandang Biaro - Jacobus, Desmiati Arisandi; Kimbal, Marthen; Waleleng, Grace (Sam Ratulangi University, 2017)
Abstract :Implementation of the program to improve the application of technology and production of nutmeg in the sub-district west siau sitaro islands regency has experienced several problems such as the procurement prototype of nutmeg draining tool, construction of nutmeg drainage site, organic fertilizer procurement, provision of nutmeg seedlings, and lack of assistance and supervision Conducted by extension officers of agriculture / plantation. The purpose of this study was to find out why the Implementation of the program to improve the application of technology and production of nutmeg in the sub-district west siau sitaro islands regency has not gone well.This research uses qualitative research method. The data source is primary data and secondary data. Primary data were obtained from direct interviews with 1 head of food and agriculture department of islands district of siau tagulandang biaro, 1 head of plantation, 1 head of production section and farmer's produce, 1 secretary of trade and labor industry service, 1 head sub extension program, 1 agricultural extension officer, 2 Head of Village, 1 Chairman and 9 Members of Farmer Group of Nutmeg. Secondary data was obtained from food and agriculture agency of siau tagulandang biaro regency in the form of data, documents, reading material and library materials related to this research. Data analysis is done by data reduction, data presentation, and conclusion.The results showed that the organizational aspects related to the work unit that is related in the implementation of the program to improve the application of technology and production of nutmeg is the implementing agency of agricultural extension of plantation and forestry in this case the role of extension officers who are in fact not maximal. Not the establishment of extension officers in one sub-district so that the task of supervision and supervision by extension officers of agriculture / plantation is not maximal. This is due to the lack of resources of agriculture / plantation extension officers in the islands districts, especially in west districts. Aspects of interpretation relate to the understanding of extension officers of agriculture / plantation who understand that this program is very important and provide their own motivation in conducting socialization, counseling, mentoring and supervision. In contrast to the fact that supervision and supervision is very rare and not routinely conducted by extension officers of agriculture / plantation and lack of self-giving from agricultural extension officers in carrying out their duties also affect the course of the program. Aspects of application in this aspect of the problem is found at the agricultural extension implementing agency for plantation and forestry in this case the extension officers of agriculture / plantation who have not performed supervision and supervision tasks routinely, so that nutmeg farmers have not been able to apply technology and ways of processing nutmeg well automatically. Assistance provided is not used by nutmeg farmers because they do not dare to accept the risk that will occur due to misuse of the assistance provided.Based on the conclusions from the results of the research and the discussion that has been suggested, it is necessary to suggest some things that is, Need additional extension of farmer / plantation extension in West Siau Subdistrict Siau Tagulandang Biaro District so that each village / one village has 1 (one) extension worker It is written in Law number 19 year 2013, so extension worker in doing socialization, counseling, mentoring and supervision activities can be done with maximum. It is incumbent on extension officers to be able to share their knowledge through study or research conducted to be transferred to the community in need in this case nutmeg farmers as beneficiaries of the program. Need to go down the field with a routine that is once a week doing mentoring and supervision.Â Keyword: implementation, technology implementation and Improvement Program production, Nutmeg